Detoxification Capacity and Protective Effects of Medicinal Plants against Heavy Metals in Polluted Human Systems: A Recent Study - Algandaby, Mardi M.; M. Al-Hadead, Khadiga; El-Darier, Salama M. (Current Aspects in Pharmaceutical Research and Development Vol. 7, 2022)
The primary goal of this study was to recommend specific herbal formulas as supplements in polluted human societies in order to reduce the harmful effects of prevailing heavy metals. The concentrations of various heavy metals in Abu Qir, Amreyya, and Abis districts were determined, as well as the various methods by which these metals were introduced into the body system. There are many ways by which heavy metals can be broadcasted into the body such as ingesting of foods, beverages, skin exposure and inhaled air. Based on the types of heavy metals and their concentrations, a herbal assemblage (ACOSTU) was created. The results of the herbal assembly application for six months showed a significant improvement in the medical examined cases recorded in the study areas. The study concluded that the implementation of health-care-specific programmes for people living in polluted areas is critical as part of a long-term development strategy to save endangered rural communities.